Relatórios contábeis e financeiros nos países em transformação: da economia planificada à economia de mercado - Rússia e China - Soares, Jairo da Rocha (2009)
This thesis is the insertion of the International Accounting study as a knowledge area of International Relations. The purpose of this study is to present a research in International Accounting, in the sphere of Russia and China, disclosing about the following theme axes: globalization in the context of accounting; the new accounting agenda; main social, political and cultural characteristics; accounting education of these two countries and their accounting standards and practices. This study demonstrated that the relative irreversibility of globalization is imbricated with the right to property adopted by Russia and by China. Another factor was the much more robust accounting agenda put into action from 1978 to 2008, with issuing of new pronouncements, whose objective was an alignment with the IASB on the convergence of the IFRS. The raising, consolidation and development of any social, political and cultural system inevitably went through a tortuous process, filled with sacrifices and fights, with successes and failures. The accounting education in these countries is still a new subject. In its favor there is the high educational background of their citizens, result of the socialist political regime. In these transformation countries the adoption of the IFRS is not merely a technical exercise involving rearrangement of information and reclassification in the financial statements, but it is a challenge to the fundaments of a centrally planned economy to the market economy. It is the moment in which the Companies and the Financial Institutions will have a unique opportunity to reexamine and reorganize their businesses. The adoption of the IFRS is not a choice of different accounting policies; it involves a different system for measuring, recognizing and evidencing of its performance with the international markets. There will be levels of increased transparency for many Companies and Financial Institutions. Adopting the IFRS allows the Companies and Financial Institutions the opportunity of remodeling the business, for example, checking how the KPI´s Key performance indicators are determined and used in the business and in which way the performance of the Companies and Financial Institutions is demonstrated in relation to the competitors from the western hemisphere. When looking towards the transformation countries, the requirement of adopting the IFRS involves a small, although important, universe of companies for what these countries represent in the economic, political, social and historical spheres of the world. Another challenge is the language barrier and also the low relevance in the study of the accounting coming from the period of centrally planned economy. Coming to a conclusion, there is a substantial conformity between CAS standards and the IFRS, as a consequence of the active participation of the Chinese authorities, but the same does not occur with the RAS and the IFRS, although mandatory for some Companies and for the Financial Institutions, due to a political and professional resistances for adoption of these standards in Russia. The Putin and Hu Jintao governments were the periods with greatest advance in the studies on accounting science that seeks to make feasible the adoption of the IFRS in the next years. The debate on the application of two simultaneous methods, the ideographic and the nomothetic, in accounting research is also unveiled